Exploring the Differential Effects of Online Reviews on Film's Box-Office Success: Source Identity and Brand Equity From an Integrated Perspective - Zhao, Kai; Yang, Xiaocong; Tao, Xiaobo; Xu, Xiaoyu; Zhao, Jinkai (Frontiers in Psychology, 2020)
This study investigates the differential effects of online reviews on actual sales in cases where information regarding source identity and brand equity is accessible. The data were collected from an influential online film review platform in China. Two distinctive features of this study are: (1) source identity is expressed as ‘verified user’ or ‘unverified user’ according to posters’ ticket payment status and (2) the interactive effect between source identity and brand equity on box-office success is examined. Using econometric estimations, the results reveal the following: (1) the positive effect of verified users’ online review valences on the number of tickets purchased for films decreases in association with high brand strength; (2) the variance of verified users’ online reviews positively affects the number of tickets purchased for films with high brand strength, but such an effect is negative with low brand strength; (3) the variance of unverified users’ online reviews positively influences the number of tickets purchased for films with low brand strength, but it negatively influences the number of tickets purchased for films with high brand strength. Thus, these findings suggest that it is better for business leaders to understand not only why producers of online reviews are satisfied or dissatisfied, but also how consumers interpret and interact with different types of online reviews and which are important. This requires a smart and flexible collaboration among different business units within film company.